1987
DOI: 10.1111/j.2042-3306.1987.tb02596.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial selection and dosage in the treatment of equine bacterial infections

Abstract: Summary The success of antimicrobial therapy depends on administration of an agent to which the pathogenic microorganisms are susceptible at the concentrations attained at the site of infection. The route of administration, size of the dose and dosing interval must be appropriate for the drug preparation selected. With penicillins in particular, dosage can be tailored to the severity of the infection and quantitative susceptibility of the microorganism. This approach cannot be applied to aminoglycosides becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…1992;Wichtel et a/. 1992) and sensitivity trends for Gram-negative equine pathogens in our hospital (Baggot and Prescott 1987; Prescott and Baggot 1988), our targeted peak and trough serum concentration for amikacin were 215 pg/ml (but <30 pg/ml) and 5 3 pg/ml (but > I pg/ml), respectively. These provided peak values which were 4-5 times the mean inhibitory concentration (MIC) for common equine pathogens and trough values below 5 pg/ml which is regarded to be the upper limit to avoid nephrotoxicity.…”
Section: Measurement Of Amikacin Serum Concentrationsmentioning
confidence: 62%
See 1 more Smart Citation
“…1992;Wichtel et a/. 1992) and sensitivity trends for Gram-negative equine pathogens in our hospital (Baggot and Prescott 1987; Prescott and Baggot 1988), our targeted peak and trough serum concentration for amikacin were 215 pg/ml (but <30 pg/ml) and 5 3 pg/ml (but > I pg/ml), respectively. These provided peak values which were 4-5 times the mean inhibitory concentration (MIC) for common equine pathogens and trough values below 5 pg/ml which is regarded to be the upper limit to avoid nephrotoxicity.…”
Section: Measurement Of Amikacin Serum Concentrationsmentioning
confidence: 62%
“…1984;Shulman and Yogev 1985;Chadwick et a/. 1986;Baggot and Prescott 1987). The emergence of gentamycin-resistant organisms (Tally et a/.…”
Section: Introductionmentioning
confidence: 99%
“…1976; National Council on Clinical Laboratory Standards 1989), previous studies on the pharmacology of amikacin in horses (Orsini et al 1985;Brown et al 1986;Adland-Davenport er al. 1990) and sensitivity trends for Gram-negative equine pathogens in our hospital (Baggot and Prescott 1987;Prescott and Baggot 1988), our targeted peak and trough serum concentrations for amikacin were I5 pg/ml and 3 @ml, respectively.…”
Section: Measurement Of Amikacin Serum Concentrationsmentioning
confidence: 82%
“…The aminoglycoside antibiotics are active against most strains of Enterohacteriaceae, Pseudornonas aeruginosa, Klehsiella spp. and Staphylococcus spp., which are common pathogens in infants and the equine neonate (Koterba et al 1984;Baggot and Prescott 1987;Shulman and Yogev 1985;Howard and McCracken 1975;Chadwick et al1986;Sardemann et al 1976). The emergence of gentamycin-resistant organisms in our hospital, and in others (Koterba et al 1984;Tally et al 1975), has necessitated the use of amikacin, a semi-synthetic aminoglycoside, for the empirical treatment of critically ill, high risk-foals.…”
Section: Introductionmentioning
confidence: 99%
“…use. Baggot and Prescott (1987) and Horspool et al. (1992) showed that intravenously administered ampicillin sodium has an elimination half‐life t 1/2 (d) of less than 1 h in the horse.…”
Section: Introductionmentioning
confidence: 99%